School to Work Transition, Employment Attainment and Vet Theories Guide for Policy Makers - Santos, Miguel (Journal of Research in Educational Sciences; Vol 1 No 2 (2010): JRES, Volume I, Issue 2(2), Winter 2010, 2010)
The employment attainment after a vocational training course, in a lifelong learning perspective is due to several factors, those inherent to the individual and those through exogenous scopes. In this theoretical revue we identify the most and the least notorious theories that can support policy maker’s decisions. This paper is a result of a subchapter of the author’s PhD thesis. The usefulness of the theories briefly described is under the reader’s verdict and judgment. The objective is barely to share a structured way to compare eleven “big groups” of theories, underneath ten different elements, that are commonly the aim of public and private policies.